A New State of Venus's Ionosphere. (15th January 2013) - Balcerak, Ernie; Schultz, Colin
Abstract : Observations from NASA's Pioneer Venus orbiter, which reached Venus in 1978, suggested that Venus's ionosphere had two states: a magnetized state with a large‐scale horizontal magnetic field and an unmagnetized state with no large‐scale magnetic field but with numerous small‐scale thin magnetic structures known as flux ropes. Venus's ionosphere was observed to be in the unmagnetized state most of the time, but strong solar wind pressure shifted it to the magnetized state.